2013
DOI: 10.1016/j.jsat.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining the temporal relationship between psychological climate, work attitude, and staff turnover

Abstract: Relative to the broader industrial-organizational (I-O) psychology field, research on the turnover of substance use disorder (SUD) treatment staff is in its infancy. Despite its long and rich history, recent reviews of the turnover literature within I-O psychology have noted there remains considerable room for improvement. In particular, recommendations have been made for research that considers time in the turnover process and explores more distal causes of staff turnover. Addressing these gaps, this paper ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…The overall response of staff was encouraging, the initial reluctance of a sizable proportion of the staff notwithstanding. The perceptions and attitudes of staff have significant impact on the success of an organization [22,23]. More so, staff satisfaction towards research and publishing practices will enhance the developmental goal and strategic management of the institution and vice versa [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall response of staff was encouraging, the initial reluctance of a sizable proportion of the staff notwithstanding. The perceptions and attitudes of staff have significant impact on the success of an organization [22,23]. More so, staff satisfaction towards research and publishing practices will enhance the developmental goal and strategic management of the institution and vice versa [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The attitude and perception of staff towards research and publishing in the institution essentially depends on job satisfaction [26]. Job satisfaction of staff in turn is influenced by research and publishing practices; research funding, research leave, research allowances, research training and development compensation, availability of amenities and professional mentorship [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…The perceptions and attitudes of staff have significant impact on the success of an organization (Tsui et al, 1997;Garner and Hunter, 2013). More so, staff satisfaction toward research and publishing practices will enhance the developmental goal and strategic management of the institution and vice versa (Bhatti and Qureshi, 2007;Tella et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The attitude and perception of staff toward research and publishing in the institution essentially depends on job satisfaction (Syed et al, 2012). Job satisfaction of staff, in turn, is influenced by research and publishing practices, research funding, research leave, research allowances, research training, and development compensation, availability of amenities, and professional mentorship (Tella et al, 2007;Garner and Hunter, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Turnover intentions precede turnover behavior and were the early focus of SA research that identified a number of predictors including co-worker support, 7 organizational functioning, 8 clinical supervision, emotional exhaustion, and organizational culture, 9,10 research participation, 11 and management practices. 12 More recent research focuses on actual turnover behavior and predictors include program-level factors, 13,14 job and pay satisfaction, 15 supervisor and co-worker support, 15 and clinician performance. 6 Eby et al also identified longitudinal patterns of turnover behavior 4,6,8 and reasons for turnover.…”
Section: Introductionmentioning
confidence: 99%